Global Poverty Goals and Prices: How Purchasing Power Parity Matters - Dean Jolliffe; Espen Beer Prydz (Institute for the Study of Labor (IZA), 2015)
With the recent release of the 2011 purchasing power parity (PPP) data from the International Comparison Program (ICP), analysts and institutions are confronted with the question of whether and how to use them for global poverty estimation. The previous round of PPP data from 2005 led to a large increase in the estimated number of poor in the world. The 2011 price data suggest that developing countries' incomes in PPP-adjusted dollars are significantly higher than indicated by the 2005 PPP data. This has created the anticipation that the new PPP data will decrease significantly the count of poor people in the world. This paper presents evidence that if the global poverty line is updated with the 2011 PPP data based on the same set of national poverty lines that define the 1.25 line in 2005 PPPs, and if the 2011 PPP conversion factors are used without adjustments to selected countries, the 2011 poverty rate is within half a percentage point of the current global estimate based on 2005 PPPs. The analysis also indicates that the goal of 'ending' extreme poverty by 2030 continues to be an ambitious one.
Keywords: I3; I32; E31; F01; 330; global poverty; International Comparisons Program; purchasing power parity